Hepatitis B birth vaccination, cohort study, Tunisia 2000–2017. Issue 1 (1st January 2020) - Dhouib, Wafa; Kacem, Meriem; bennasrallah, Cyrine; Ben Fredj, Manel; Abroug, Hela; Zemni, Imen; Chelly, Souhir; Maalel, Issam; Samia, Grira Said; Belguith Sriha, Asma
ABSTRACT: We aimed to compare the efficiency of the first dose of Hepatitis B (HB) vaccine: at Birth versus at 3 months and to evaluate the efficacy of HB vaccine. We conducted a cohort study in the governorate of Monastir. Vaccinated Cohort (VC) included populations receiving the first dose at 3 months (Protocol 1), and at birth (HepB-BD) (Protocol 2). First dose was followed by at least two doses. We collected, from January 2000 to December 2017, cases diagnosed by serological markers (hepatitis B surface antigen (HBsAg) and anti-HBc). We calculated Absolute Risk (AR) per 100, 000 PY and the Relative risk reduction (RRR). Twenty-five cases were notified among VC and 1501 cases among not vaccinated cohort (NVC). Twenty-three cases were notified among the cohort receiving the first dose at 3 months and two cases in Protocol 2. The AR per 100, 000 PY was 5.67 (CI95%: 3.36–7.99) in Protocol 1 and 0.11 (CI95%: 0.001–0.26) in Protocol 2. The RRR was 77% (95% CI: 66; 85) in Protocol 1 and 99.4% (95% CI: 97.8; 99.9) in Protocol 2. We identified 4 HB cases for children aged between 5 and 11 who benefited from protocol 1 (born between 2000 and 2006) and zero cases for children of the same age group benefiting from protocol 2 (born between 2011 and 2017). The annual number of HB has decreased from 112 in 2000 to 48 in 2017. We predicted 40 new cases of HB in 2030. HepB-BD was 99.4% effective at preventing HB. The continuity of HepB-BD worldwide would achieve WHO's goal of eliminating HB as a threat to health by 2050. Abbreviations: AR: Absolute Risk; ARR: Absolute Risk Reduction; G1: Group1; G2: Group2; HB: Hepatitis B; HepB-BD: Hepatitis B Birth Dose; MENA: Middle East and North Africa; NNV: Number Needed to Vaccine; HIV: Human Immunodeficiency Virus; NVC: Not Vaccinated Cohort; PY: Person Year; RRR: Relative Risk Reduction; RR: Relative Risk; VC: Vaccinated Cohort; WHO: World Health Organization